Surface with Switchable Wettability - LIU Peng-bo; WANG Jia-jun; FENG Lian-fang; GU Xue-ping (Cailiao gongcheng, 2016)
Superhydrophobicity and superhydrophilicity are extreme properties of solid surface governed by surface morphology and surface chemistry. Switching between superhydrophobicity and superhydrophilicity can be achieved by applying external stimuli and exchanging counterions due to the change in surface morphology and/or surface chemistry. This review mainly gives a concise overview of switchable wettability of surface. Through applying external stimuli such as light, temperature, pH value, solvent, electric potential and exchanging of counterions, the wettability of surface can switch between superhydrophobicity and superhydrophilicity. The material with asymmetric wettability exhibits some novel abilities such as directional liquid transport. Finally, the advances of surface with switchable wettability are prospected. By controlling the micro-nano structure and chemical composition, the switch between superhydrophobicity and superhydrophilicity can be realized on various surfaces.